2020
DOI: 10.3892/mmr.2020.11142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR‑195‑5p on cell proliferation and apoptosis in gestational diabetes mellitus via targeting EZH2

Abstract: Gestational diabetes mellitus (GdM) is a type of diabetes mellitus (dM) that occurs during pregnancy. The present study aimed to investigate the roles of microrna (mir)-195-5p and enhancer of zeste homolog 2 (eZH2) in GdM, and their potential association. Human umbilical vein endothelial cells (HuVecs) were collected from healthy and GdM umbilical cords, and the endothelial properties were detected by flow cytometry. mRNA expression levels of miR-195-5p and EZH2, and EZH2 protein expression levels were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Expression of miR-101-3p, a pancreatic islet-enriched miRNA with a role in insulin secretion and β cell functioning [ 85 ], is demonstrated to be regulated by H3K27me3 modification in EZH2. Moreover, epigenetically regulated alterations in miRNAs induced by suboptimal maternal nutrition or endocrine factors are also reported to be responsible for altered gene expression and to promote offspring and adult MetS phenotypes [ 86 , 87 ]. Altogether, these studies provide evidence for a functional link between classical epigenetic regulations of miRNA underpinning pathophysiological processes characterised as causal factors in the development of MetS.…”
Section: Epigenetics and Mirnas In Metsmentioning
confidence: 99%
“…Expression of miR-101-3p, a pancreatic islet-enriched miRNA with a role in insulin secretion and β cell functioning [ 85 ], is demonstrated to be regulated by H3K27me3 modification in EZH2. Moreover, epigenetically regulated alterations in miRNAs induced by suboptimal maternal nutrition or endocrine factors are also reported to be responsible for altered gene expression and to promote offspring and adult MetS phenotypes [ 86 , 87 ]. Altogether, these studies provide evidence for a functional link between classical epigenetic regulations of miRNA underpinning pathophysiological processes characterised as causal factors in the development of MetS.…”
Section: Epigenetics and Mirnas In Metsmentioning
confidence: 99%
“…The molecular mechanisms by which EZH2 may affect endothelial-dependent atherogenesis are gaining attention. The independent atherosclerosis risk factors dyslipidaemia [ 130 ], hyperhomocysteinemia, [ 144 ] hyperglycaemia [ 156 ] and OSS [ 110 ] all block the expression of endothelial microRNAs that repress EZH2 translation under physiological conditions. For example, in human umbilical vein endothelial cells (HUVECs) treated with oxLDL, miR-200a expression is decreased, causing an upregulation of EZH2 [ 130 ].…”
Section: The Endothelial Transcriptome As a Target For Anti-atheromentioning
confidence: 99%
“…For example, in human umbilical vein endothelial cells (HUVECs) treated with oxLDL, miR-200a expression is decreased, causing an upregulation of EZH2 [ 130 ]. During hyperhomocysteinemia, levels of EZH2 are increased as a result of reduced levels of miR-92a [ 144 ] and upon OSS, miR-101 expression is downregulated [ 110 , 157 ] also leading to an increased expression of endothelial EZH2 and the concurrent H3K27Me3 [ 130 , 144 , 156 ]. Interestingly, in the field of oncology, multiple other microRNAs such as miR-26a, miR-124 and miR-214 have been described to repress EZH2 expression [ 158 , 159 ].…”
Section: The Endothelial Transcriptome As a Target For Anti-atheromentioning
confidence: 99%
See 1 more Smart Citation
“…They found that 11 miRNAs (including hsa-miR-1299, hsa-miR-1200, hsa-miR-578, hsa-miR-593-5p, hsa-miR-765, hsa-miR-520d-3p, hsa-miR-617, hsa-miR-92a-3p, hsa-miR-30b-5p, hsa-miR-181c-5p, and hsa-miR-181a-5p) differed in their expression ( 99 ), indicating their potential role in GDM; however, future studies are needed to elucidate this further. Additionally, miR-195-5p was up-regulated in GDM-induced HUVECs, inhibited cell viability and proliferation, and promoted apoptosis by targeting EZH2 in vitro ( 72 ), thus highlighting the importance of miRNAs in GDM.…”
Section: Role Of Non-coding Rnas and Evs In Gdmmentioning
confidence: 99%